PEMAMFAATAN HARTA WAKAF DALAM PENGEMBANGAN EKONOMI MASYARAKAT (Studi Kasus Terhadap Masyarakat Desa Gampong Baroe Peusangan Kabupaten Bireuen) - Ibrahim Ibrahim; Zawil Ihda (STIS Nahdlatul Ulama Aceh, 2021)
Waqf is a religious institution that is closely related to socio-economy, waqf has helped a lot in human resource development and social resource development. It cannot be denied that most houses of worship, Islamic colleges and Islamic religious institutions are built on waqf land. As one of the aspects of Islamic teachings that have a spiritual dimension, waqf is also a target that emphasizes the importance of economic prosperity, namely by making waqf property or the residue of the waqf land that has been used as waqf which is more productive (yielding) which results can be used for common interests. This study aims to determine the use of waqf assets for economic development and the management and utilization of waqf assets. This type of research is qualitative research, while the data analysis uses a descriptive approach. The results showed that the waqf land management system in Gampong Baro Village was generally still traditional. Most of the donated land is used for religious and educational activities. However, now the vacant land is used as a place for convection and burning of bricks with capital from the leasing of waqf land, strategic land is developed to build shop houses from BUMG funds which are then leased.